Health literacy and its relation to continuing with breastfeeding at six months post‐partum in a sample of Spanish women - María Jesús Valero‐Chillerón; Victor M. González‐Chordà; Águeda Cervera‐Gasch; Rafael Vila‐Candel; Francisco Javier Soriano‐Vidal; Desirée Mena‐Tudela (Wiley, 2021)
Abstract Aim To explore the relation between health literacy (HL) and continuing breastfeeding (BF) at 6 months post‐partum. Design Observational, longitudinal and prospective study between December 2018-May 2019. The STROBE checklist was used. Methods 114 mother/baby pairings from a Spanish Hospital were included. Mothers' health literacy was studied with the Newest Vital Sign and Short Assessment of Health Literacy for Spanish Adults 50 (SAHLSA‐50). Before hospital discharge, BF efficiency was studied using the LATCH BF score and BF continuity was followed for 6 months. Survival analysis and Cox regression were done. Results Health literacy levels and BF effectiveness were adequate before hospital discharge. At 6 months post‐partum, less than half the sample still exclusively breastfed. The main reason for early exclusive BF cessation was lower than the recommended newborn weight gain. The HL level acted as a protective factor against abandonment of BF.